HUKUMAN MATI MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA DALAM PERSPEKTIF HAK ASASI MANUSIA - Daffa Rizky Dewanto; Rahtami Susanti (Wijayakusuma Law Review, 2023)
Indonesia is a country that acknowledges the existence of Human Rights, but this does not lead to the abolishment of the death penalty in its positive law. Both the old and new Criminal Codes (KUHP) still regulate the death penalty, albeit in different concepts. This research aims to identify the differences between the death penalty in the old and new Criminal Codes and to understand and analyze the death penalty in the new Criminal Code from a human rights perspective. The research employs a normative juridical method. The findings indicate that the death penalty in the new Criminal Code is no longer the primary punishment as in old Criminal Codes and has been replaced with an alternative penalty. Under the new Criminal Code, those sentenced to death will undergo a probationary period of 10 (ten) years, and if they demonstrate good behavior during this period, the death penalty will be commuted to life imprisonment or imprisonment for 20 (twenty) years. This change is motivated by the perception that the death penalty constitutes a violation of human rights. Keyword: death penalty, Indonesian new penal code, human rights Indonesia merupakan negara yang mengakui eksistensi Hak Asasi Manusia namun hal tersebut tidak membuat Indonesia menghapus hukuman mati dalam hukum positif di Indonesia. Baik KUHP lama maupun KUHP baru masih mengatur hukuman mati meskipun dalam konsep yang berbeda. Penelitian ini bertujuan untuk mengetahui perbedaan hukuman mati dalam KUHP lama dan KUHP baru serta mengetahui dan menganalisis hukuman mati dalam KUHP baru dalam perspektif hak asasi manusia. Penelitian ini menggunakan metode yuridis normatif. Hasil penelitian menunjukkan bahwa pidana mati dalam KUHP baru tidak menjadi pidana pokok sebagaimana dalam KUHP lama dan beralih menjadi pidana alternatif. Terpidana mati dalam KUHP baru akan menjalani masa percobaan selama 10 (sepuluh) tahun dan apabila selama masa percobaan terpidana terbukti berbuat baik pidana diubah menjadi penjara seumur hidup atau pidana penjara selama 20 (dua puluh) tahun. Hal ini dilatarbelakangi adanya persepsi bahwasanya pidana mati merupakan pelanggaran HAM. Kata kunci: hukuman mati, KUHP baru, hak asasi manusia